Comparative chemical array screening for p38γ/δ MAPK inhibitors using a single gatekeeper residue difference between p38α/β and p38γ/δ - Kondoh, Yasumitsu (Sci Rep, 2016)
Mammalian p38 mitogen activated protein kinases (MAPKs) are responsive to a variety of cellular stresses. The development of specific pyridinyl imidazole inhibitors has permitted the characterization of the p38 MAPK isoform p38α, which is expressed in most cell types, whereas the physiological roles of p38γ and p38δ are poorly understood. In this study, we report an approach for identifying selective inhibitors against p38γ and p38δ by focusing on the difference in gatekeeper residues between p38α/β and p38γ/δ. Using GST-fused p38α wild type and T106M mutant constructs, wherein the p38α gatekeeper residue (Thr-106) was substituted by the p38γ/δ-type (Met), we performed comparative chemical array screening to identify specific binders of the mutant and identified SU-002 bound to p38αT106M specifically. SU-002 was found to inhibit p38αT106M but not p38α kinase activity in in vitro kinase assays. SU-005, the analog of SU-002, had inhibitory effects against the kinase activity of p38γ and p38δ in vitro but not p38α. In addition, SU-005 inhibited both p38γ and p38δ auto-phosphorylation in HeLa and HEK293T cells. These results demonstrate that the comparative chemical array screening approach is a powerful technique to explore specific inhibitors for mutant proteins with even single amino-acid substitutions in a high-throughput manner.